Analysis of Income and Feasibility of Rice Farming in Kepuhdoko Village Jombang - Afifuddin Afif; Yessita Puspaningrum; Miftachul Chusnah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the income level and financial feasibility of rice farming in Kepuhdoko Village, Tembelang District, Jombang Regency. Rice farming is the primary livelihood of most rural communities and plays a significant role in supporting household income. However, farmers face various challenges such as rising production costs, limited labor, and fluctuating selling prices. This research employed a survey method with a simple random sampling technique involving 30 rice farmers. Primary data were collected through structured interviews, while secondary data were obtained from related institutions and literature. Data analysis included production cost analysis, revenue analysis, income calculation, and business feasibility using the Revenue Cost Ratio (R/C Ratio). The results indicate that the average total revenue per planting season is IDR 15,771,609 with total production costs of IDR 3,310,455, resulting in a net income of IDR 12,461,154 per season. The R/C Ratio value of 4.95 shows that rice farming in the study area is economically feasible and highly profitable. These findings confirm that small-scale rice farming remains financially viable when managed efficiently and supported by good productivity and favorable market prices. Keywords: Income; Feasibility; Rice Farming; R/C Ratio